Discovery of Substituted Hydroxylphenyl Pyrimidine-2(1H) Thione as a New Series of Antioxidant using AAU and AAI Method - DUDHE, Rupesh; SHARMA, Pramod Kumar; VERMA, Prabhaker Kumar (Walailak Journal of Science and Technology (WJST), 2014)
A series of substituted pyrimidine has been discovered as a new class of potent antioxidant. 6-(Substituted aldehyde)- 3,4-dihydro-1-(tetrahydro-3,4-dihydroxy-5-hydroxymethyl)furan-2-yl)-4-(4-hydroxyphenyl)pyrimidine-2(1H)-thione derivative (XVII-XXIV) was synthesized from the 6-(Substituted aldehyde) -4-phenylpyrimidine-2(1H)-thione derivative (IX-XVI) through the reaction mechanisms of Claisen-Schmidt, Cyclization and Satos fusion. The structures of the synthesized compounds were elucidated by I.R., 1H-NMR, elemental analysis and mass spectroscopic techniques. The synthesized compounds were screened for in vitro antioxidant activity using the DPPH assay, based on the AAI and AAU, using a combination relation between DPPH concentration and absorbance. The antioxidant strength of compounds was compared against ascorbic acid. Among them, compounds XVII, XX, XIX and XXIV exhibited significant antioxidant activity, as seen by using the free radical scavenging (DPPH) method. doi:10.14456/WJST.2015.83